Deregulation of the actin cytoskeleton and macropinocytosis in response to phorbol ester by the mutant protein kinase C gamma that causes spinocerebellar ataxia type 14 - Yamamoto, Kazuhiro; Seki, Takahiro; Yamamoto, Hikaru; Adachi, Naoko; Tanaka, Shigeru; Hide, Izumi; Saito, Naoaki; Sakai, Norio (Frontiers in Physiology, 2014)
Several missense mutations in the protein kinase Cγ (γPKC) gene have been found to cause spinocerebellar ataxia type 14 (SCA14), an autosomal dominant neurodegenerative disease. γPKC is a neuron-specific member of the classical PKCs and is activated and translocated to subcellular regions as a result of various stimuli, including diacylglycerol synthesis, increased intracellular Ca2+ and phorbol esters. We investigated whether SCA14 mutations affect the γPKC-related functions by stimulating HeLa cells with TPA (12-O-tetradecanoylpholbol 13-acetate), a type of phorbol ester. Wild-type (WT) γPKC-GFP was translocated to the plasma membrane within 10 min of TPA stimulation, followed by its perinuclear translocation and cell shrinkage, in a PKC kinase activity- and microtubule-dependent manner. On the other hand, although SCA14 mutant γPKC-GFP exhibited a similar translocation to the plasma membrane, the subsequent perinuclear translocation and cell shrinkage were significantly impaired in response to TPA. Translocated WT γPKC colocalized with F-actin and formed large vesicular structures in the perinuclear region. The uptake of FITC-dextran, a marker of macropinocytosis, was promoted by TPA stimulation in cells expressing WT γPKC, and FITC-dextran was surrounded by γPKC-positive vesicles. Moreover, TPA induced the phosphorylation of MARCKS, which is a membrane-substrate of PKC, resulting in the translocation of phosphorylated MARCKS to the perinuclear region, suggesting that TPA induces macropinocytosis via γPKC activation. However, TPA failed to activate macropinocytosis and trigger the translocation of phosphorylated MARCKS in cells expressing the SCA14 mutant γPKC. These findings suggest that γPKC is involved in the regulation of the actin cytoskeleton and macropinocytosis in HeLa cells, while SCA14 mutant γPKC fails to regulate these processes due to its reduced kinase activity at the plasma membrane. This property might be involved in pathogenesis of SCA14.